Performance Sports Group : to invest or not to invest - Jackson, Erin P.; Ciulla, Stefania; Ehlen, Frederik; Ogunlana, Ayobami; Dixon, Jess C. (London : Human Kinetics, Inc., 2017)
In August of 2015, Felix Farmer received notice that he would be inheriting a large sum of money from his great-uncle's will. Farmer is contemplating investing $50,000 CAD ($38,251 USD) of his inheritance in the parent company of his favorite hockey brand, Bauer. Performance Sports Group (PSG) is a leading manufacturer in the global sporting goods industry that is publicly traded on both the Toronto and New York Stock exchanges, and the parent of such highly successful brands as Bauer and Easton. This case study challenges students to calculate financial ratios, apply various other financial analyses to understand the financial performance of PSG, and complete a Porter's (2008) Five Forces industry analysis as a means of deciding whether Farmer should invest a portion of his inheritance with PSG.
Originally Published InJackson, E. P., Ciulla, S., Ehlen, F., Ogunlana, A., & Dixon, J. C. (2017). Performance Sports Group: To invest or not to invest. Case Studies in Sport Management, 6(1), 76-85.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Farmer, Felix; Performance Sports Group; Sports -- Economic aspects -- Case studies; Business forecasting -- Case studies; Investments -- Case studies